The Right of The Guardian to Ijbar And The Principle of Consent in Islamic Law - Zainul Mushthofa; Siti Aminah (LPPM Ma'had Aly Sunan Drajat Lamongan, 2025)
Phenomenon wedding early in Bluri Village, District Solokuro, Lamongan Regency, reflects reality social where tradition matchmaking and pressure economy Still become factor dominant in determine age marriage. Research This aim For analyze background behind social, views figure society, as well as implications law and religion of practice wedding early consequence parental coercion. Approach used is qualitative descriptive with method interviews, observations, and documentation. Research results show that practice wedding early in Bluri Village driven by four factor main, namely economy, tradition matchmaking, low education, and moral concerns. Although public look at wedding as form not quite enough responsibility and honor, in a law practice This contradictory with Constitution Number 16 of 2019, as well as religiously not reflect principle ridha ( willingness ) and the benefits that arise base wedding in Islam. Therefore that, is necessary effort awareness proportional law and religious education For prevent occurrence wedding children under future age.